A dignified passage through the gates of Hades : the burial custom of cremation and the warrior order of Ancient Eleutherna - Agelarakis, Anagnostis P., 1956- (Access archaeology., 2016)
This work examines the burial customs of cremation of the Warrior Order of Ancient Eleutherna.